2018
DOI: 10.1007/s10103-018-2471-3
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects

Abstract: The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 36 publications
4
80
0
2
Order By: Relevance
“…Becorpi at al studied the vaginal microbiome in 20 breast cancer survivors treated with two sessions of CO 2 LASER. The study reported an almost unchanged microbiome following treatment.…”
Section: Basic Science Evidencementioning
confidence: 99%
“…Becorpi at al studied the vaginal microbiome in 20 breast cancer survivors treated with two sessions of CO 2 LASER. The study reported an almost unchanged microbiome following treatment.…”
Section: Basic Science Evidencementioning
confidence: 99%
“…All reported an improvement compared to baseline. Sexual function was reported to improve in thirteen studies . Improvement increased in proportion to the number of treatments and results lasted 6 months following the first treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies used the VHIS . All reported a statistically significant improvement, regardless of whether it was one or up to three laser treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further high-quality studies are currently being undertaken. In some women for whom estrogen is contraindicated, vaginal laser treatment may have a definite role; several small studies have demonstrated efficacy in breast cancer survivors, [10][11][12][13][14][15] but the quality of the evidence remains poor.…”
Section: Genitourinary Syndrome Of the Menopausementioning
confidence: 99%